Towards a renewal of the Marxist Theory of Value : Recent debates (2020)
This text is inscribed in the debates raised by the new and growing interest in the economic theses of Karl Marx and, especially, in his Labor Theory of Value. The notion that animates this text argues that the multiple objections that have been raised about it actually point to versions and formalizations that correspond more to Ricardo's elaborations. Marx considered that his own version on the theory of value was not only different, but much more advanced and rigorous than that of his predecessor. In this text it is proposed that the new explorations on the theory of value, very promising for a critical interpretation of capitalism, rely decisively on reinterpretations of Marx in which elements of his reflection that have been eliminated by later thinkers, both supporters and contradictors, are rescued, and are developed and adapted for present times. The text consists of a succinct reconstruction of the main milestones of the development of the Theory of Labor Value, interpreted from this perspective, which raises versions that are different to the most widespread ones. Thus the formulations of this theory elaborated by Smith, Ricardo and Marx are examined. From a current perspective, the questions raised around the debate on the Transformation of Values in Prices are analyzed mainly those developed by Bortkiewicz and later by Sraffa and the Neoricardian School. It includes also a reflection on the conceptions in this regard of the ¿ 20th-century Marxism¿, dominant in the mainstream of Marxism during a long tima, which here is argued that they are de facto closer to Ricardo than Marx. Two contemporary neo-Marxist currents are examined, the "New Approach" and the "sequentialists" (of the Temporal Single System analysts) that are intended precisely to present new developments from reinterpretations of Marx's theses. The text ends with the presentation of some original pieces of analysis that have this same perspective, which are partially supported by neo-Marxist formulations, but also consist in reelaborations of different moments of this tradition. It points to contribute to the formulation of an Abstract Labor Theory of Value.